2016
DOI: 10.1371/journal.pone.0151199
|View full text |Cite
|
Sign up to set email alerts
|

Severe Community-Acquired Pneumonia Caused by Human Adenovirus in Immunocompetent Adults: A Multicenter Case Series

Abstract: BackgroundSevere community-acquired pneumonia (CAP) caused by human adenovirus (HAdV), especially HAdV type 55 (HAdV-55) in immunocompetent adults has raised increasing concerns. Clinical knowledge of severe CAP and acute respiratory distress syndrome induced by HAdV-55 is still limited, though the pathogen has been fully characterized by whole-genome sequencing.MethodsWe conducted a multicentre retrospective review of all consecutive patients with severe CAP caused by HAdV in immunocompetent adults admitted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
77
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(81 citation statements)
references
References 29 publications
3
77
0
1
Order By: Relevance
“…2 Clarifying the circulation of Ad14 and Ad55 nAbs in general populations is essential for understanding the herd immunity. Here, we investigated the seroprevalence of Ad14 and Ad55 nAbs in a large cohort from Southern China, and we found that the seropositive rates of Ad14 and Ad55 were much lower than that of Ad5 according to our previous results.…”
Section: Discussionmentioning
confidence: 99%
“…2 Clarifying the circulation of Ad14 and Ad55 nAbs in general populations is essential for understanding the herd immunity. Here, we investigated the seroprevalence of Ad14 and Ad55 nAbs in a large cohort from Southern China, and we found that the seropositive rates of Ad14 and Ad55 were much lower than that of Ad5 according to our previous results.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies have reported that patients with community-acquired pneumonia and adenovirus infection have mean age that ranges from 30 to 38 years old. 52,53 Adenovirus also causes serious infection in immunocompromised patients. The adenovirus species found in immunocompromised patients are not typically found in the community, which indicates endogenous viral reactivation in these patients.…”
Section: Adenovirusmentioning
confidence: 99%
“…169 In a retrospective review, the use of corticosteroids in immunocompetent patients with adenovirus pneumonia did not show any benefit. 172…”
Section: Adenovirusmentioning
confidence: 99%